Device-measured postpartum sleep and breastfeeding contexts among women in urban Vietnam - Yunhee Kang; Minsol Kim; Toan Thi Nguyen; Ahreum Choi; Heeyeon Kim; Tuan Minh Vo (Frontiers in Public Health, 2026)
Introduction Postpartum sleep patterns are embedded within complex caregiving environments, including infant feeding, nighttime caregiving demands, and maternal recovery. This cross-sectional study aimed to characterize maternal sleep patterns and explore variation in sleep across infant feeding contexts, exclusive and partial breastfeeding practices among women at 1 month postpartum in Ho Chi Minh City, Vietnam. Methods Sleep patterns were assessed using a commercial wearable device, and reported breastfeeding indicators included exclusive breastfeeding (EBF) status, feeding frequency during day and nighttime, and breast milk expression practices. Adjusted linear and logistic regression analyses were used, adjusting for covariates. Results The average daily sleep duration was 5.53 hours (SD: 1.36), falling substantially below adult recommendations. The prevalence of EBF was 47.7%, with mothers breastfeeding an average of 6.8 times (SD: 1.3) during the day and 2.8 times (SD: 0.6) at night. After adjusting for socio-demographic, reproductive, and caregiving-related covariates, feeding group was not significantly associated with either device-measured sleep duration (adjusted β = −0.31, 95% CI: −0.68, 0.06) or the likelihood of sleeping ≥5 hours (adjusted PR = 0.94, 95% CI: 0.65, 1.36). Also, there were no statistically significant associations between daytime or nighttime breastfeeding frequency or pumping frequency and sleep duration. Discussion These findings highlight the complexity of postpartum sleep within real-world caregiving environments, suggesting that factors beyond feeding practices alone may contribute to variation in maternal sleep. This study provides empirical insights into maternal sleep in an urban LMIC setting and highlights the growing role of wearable devices in assessing postpartum sleep.